Numerical Study on the Formation and Solidification of LMPA Microdroplet in a Microfluidic Device - Guo, Yanhong; Ren, Yong; Hou, Tuo; Wang, Jing; Wang, Chengbo (Frontiers in Energy Research, 2022)
LMPA droplets or particles have contributed to many fields such as the application of sensors and valves, and droplet-based microfluidics has been applied to the preparation of LMPA droplets. Understanding how flow rate, interfacial tension, and temperature affect the formation and solidification of droplets is helpful to design a microfluidic platform. In this study, a coupled VOF and enthalpy-porosity method will be used to numerically simulate how these factors affect the LMPA droplet formation and solidification process. We find that increasing the velocity of the continuous phase or decreasing the interfacial tension will reduce the LMPA droplet size and simultaneously increase the frequency of droplet formation. In addition, increasing the interfacial tension will decrease the required solidification time of LMPA droplets, and the solidification time of droplets will first increase and then decrease with the growth of continuous-phase velocity. On the other hand, increasing the continuous-phase temperature or cooling wall temperature will reduce the solidification time of LMPA droplets, but has no obvious influence on the size and frequency of droplet generation.